(untitled) (Research, Society and Development, 2022)
Introduction: Guillain-Barré Syndrome (GBS) is defined as an acute demyelinating inflammatory polyradiculoneuropathy, which affects the nerve roots and peripheral nerves, causing ascending, progressive, symmetrical and bilateral motor weakness, which may affect the lower and upper limbs. , respiratory muscles, trunk and face. Objective: To analyze the physical therapy approach in Guillain-Barré Syndrome. Methods: This is an integrative review that selected articles published in journals indexed in the Virtual Health Library (VHL), PubMed and Google Scholar. Results: 8 articles were selected from databases in English, Portuguese and Spanish, with publication date between 2010 and 2021; free articles available in full and full texts dealing with physical therapy treatment in Guillain-Barré syndrome (GBS). Conclusion: It is concluded that early physical therapy treatment is essential in the recovery of patients with GBS, providing an improvement in motor functionality, aiming at a greater performance of activities of daily living, in addition to the importance of intensive multidisciplinary intervention in the rehabilitation process.